2021
DOI: 10.3390/jpm11121285
|View full text |Cite
|
Sign up to set email alerts
|

What’s New in Cirrhotic Cardiomyopathy?—Review Article

Abstract: Cirrhotic cardiomyopathy (CCM) is a relatively new medical term. The constant development of novel diagnostic and clinical tools continuously delivers new data and findings about this broad disorder. The purpose of this review is to summarize current facts about CCM, identify gaps of knowledge, and indicate the direction in which to prepare an updated definition of CCM. We performed a review of the literature using scientific data sources with an emphasis on the latest findings. CCM is a clinical manifestation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 82 publications
(130 reference statements)
0
6
0
Order By: Relevance
“…had CCM, and in group III, 7 (35%) patients had CCM, with no significant difference between the three groups. The previously mentioned data is demonstrated in Table (4).…”
Section: Original Researchmentioning
confidence: 88%
See 1 more Smart Citation
“…had CCM, and in group III, 7 (35%) patients had CCM, with no significant difference between the three groups. The previously mentioned data is demonstrated in Table (4).…”
Section: Original Researchmentioning
confidence: 88%
“…A comparison of the criteria for the diagnosis of CCM is shown in Table (1). [4] Regarding the pathophysiology of CCM, it has been suggested that a hyperdynamic circulation initially compensates for the significant splanchnic arterial vasodilatation seen in liver cirrhosis; subsequently, liver disease progression and portal hypertension leads to additional splanchnic vasodilatation and a reduced effective arterial blood volume, which triggers the sympathetic nervous system and the renin-angiotensin-aldosterone system. Overexposure to sympathetic effector molecules results in downregulation, internalization, and cardiac damage, which impairs the function of β-adrenergic receptors [5].…”
Section: Original Researchmentioning
confidence: 99%
“…with oxygen therapy, sodium restriction, and diuretics. 105 Besides reducing the risk of bleeding from oesophageal varices, 106 β-blockers alleviate systemic inflammation by reducing portal pressure, mesenteric venous congestion and intestinal permeability, thereby reducing the entry of inflammatory cytokines into the circulation. The alleviation of systemic inflammation may benefit the heart.…”
Section: Therapeutic Strategiesmentioning
confidence: 99%
“…PRS complicates 8%-30% of LT and manifests as dramatic reductions in the heart rate, cardiac output and systemic vascular resistance, leading to systemic hypotension, and in some cases dysrhythmias or even cardiac arrest[ 16 ]. Although the pathogenesis of PRS remains unclear, different mechanisms have been implicated with most important being the rapid release of vasoactive substances and pro-inflammatory cytokines [tumor necrosis factor (TNF)-1α, interleukin (IL)-6] from both the donor graft and the recipient’s immune system[ 16 , 17 ].…”
Section: Hemodynamic Changes During Ltmentioning
confidence: 99%